Magnetic gold nanotriangles by microwave-assisted polyol synthesis. Issue 33 (4th August 2015) - Yu, Siming; Hachtel, Jordan A.; Chisholm, Matthew F.; Pantelides, Sokrates T.; Laromaine, Anna; Roig, Anna
Abstract : A facile, fast and bio-friendly microwave-assisted polyol route to synthesize high yield magnetic gold nanotriangles. Abstract : Simple approaches to synthesize hybrid nanoparticles with magnetic and plasmonic functionalities, with high control of their shape and avoiding cytotoxic reactants, to target biomedical applications remain a huge challenge. Here, we report a facile, fast and bio-friendly microwave-assisted polyol route for the synthesis of a complex multi-material consisting of monodisperse gold nanotriangles around 280 nm in size uniformly decorated by superparamagnetic iron oxide nanoparticles of 5 nm. These nanotriangles are readily dispersible in water, display a strong magnetic response (10 wt% magnetic fraction) and exhibit a localized surface plasmon resonance band in the NIR region (800 nm). Moreover, these hybrid particles can be easily self-assembled at the liquid–air interfaces.